Small Near-Earth Asteroids in the Palomar Transient Factory Survey: A Real-Time Streak-detection System. (7th February 2017) - Waszczak, Adam; Prince, Thomas A.; Laher, Russ; Masci, Frank; Bue, Brian; Rebbapragada, Umaa; Barlow, Tom; Surace, Jason; Helou, George; Kulkarni, Shrinivas
Abstract: Near-Earth asteroids (NEAs) in the 1–100 meter size range are estimated to be ∼1, 000 times more numerous than the ∼15, 000 currently cataloged NEAs, most of which are in the 0.5–10 kilometer size range. Impacts from 10–100 meter size NEAs are not statistically life-threatening, but may cause significant regional damage, while 1–10 meter size NEAs with low velocities relative to Earth are compelling targets for space missions. We describe the implementation and initial results of a real-time NEA-discovery system specialized for the detection of small, high angular rate (visually streaked) NEAs in Palomar Transient Factory (PTF) images. PTF is a 1.2-m aperture, 7.3 deg 2 field of view (FOV) optical survey designed primarily for the discovery of extragalactic transients (e.g., supernovae) in 60-second exposures reaching ∼20.5 visual magnitude. Our real-time NEA discovery pipeline uses a machine-learned classifier to filter a large number of false-positive streak detections, permitting a human scanner to efficiently and remotely identify real asteroid streaks during the night. Upon recognition of a streaked NEA detection (typically within an hour of the discovery exposure), the scanner triggers follow-up with the same telescope and posts the observations to the Minor Planet Center for worldwide confirmation. We describe our 11 initial confirmed discoveries, all small NEAs that passed 0.3–15 lunar distances from Earth. Lastly, we derive useful scaling laws for comparing streaked-NEA-detection capabilities of different surveys as a function of their hardware and survey-pattern characteristics. This work most directly informs estimates of the streak-detection capabilities of the Zwicky Transient Facility (ZTF, planned to succeed PTF in 2017), which will apply PTF's current resolution and sensitivity over a 47-deg 2 FOV.